2008
DOI: 10.1002/prca.200780151
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of human proximal tubular cells exposed to high glucose concentrations

Abstract: Hyperglycemia is a major key factor in the pathogenesis of microvascular complications of diabetes, including diabetic nephropathy (DN). Most studies to date have focused on the glomerular abnormalities found in DN. However, nephromegaly in the early stages of diabetes and the correlation of tubulointerstitial pathology rather than glomerular pathology with declining renal function in DN suggests the involvement of the tubulointerstitium. The etiology of the tubulointerstitial pathology in DN, however, is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…Several analyses of the renal proteome with regard to DN have been conducted, including studies of the renal cortex (Tilton et al 2007), renal proximal tubular epithelial cells (So et al 2008), and urinary proteins (Rao et al 2007). Furthermore, one current study showed differential proteomic changes in an immortalized mouse podocyte cell line after long term exposure (two weeks) to HG (Schordan et al 2009).…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Several analyses of the renal proteome with regard to DN have been conducted, including studies of the renal cortex (Tilton et al 2007), renal proximal tubular epithelial cells (So et al 2008), and urinary proteins (Rao et al 2007). Furthermore, one current study showed differential proteomic changes in an immortalized mouse podocyte cell line after long term exposure (two weeks) to HG (Schordan et al 2009).…”
Section: Discussionmentioning
confidence: 68%
“…2-DE analysis and protein identification were conducted following a previously described procedure (So et al 2008). Isoelectric focusing (IEF) was performed using Immobiline DryStrips (24 cm, pH 3-10 NL, GE healthcare, USA) and fifty micrograms of the sample were loaded onto each strip.…”
Section: -De Analysismentioning
confidence: 99%
See 3 more Smart Citations